Hardware-software complex for sports orientation, selection and stage control: potential for judo and sambo - Koryagina, Y. V.; Nopin, S. V.; Ter-Akopov, G. N.; Abutalimova, S. M. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and implement an information system - hardware-software complex for sports orientation, selection and stage control in judo and sambo.